Sudan black: a fast, easy and non‐toxic method to assess myelin repair in demyelinating diseases. (10th March 2017) - Ineichen, Benjamin V.; Weinmann, Oliver; Good, Nicolas; Plattner, Patricia S.; Wicki, Carla; Rushing, Elisabeth J.; Linnebank, Michael; Schwab, Martin E.
Abstract : Aims: The search for novel drugs that enhance myelin repair in entities such as multiple sclerosis has top priority in neurological research, not least because remyelination can hinder further neurodegeneration in neuro‐inflammatory conditions. Recently, several new compounds with the potential to boost remyelination have been identified using high‐throughput in vitro screening methods. However, assessing their potential to enhance remyelination in vivo using plastic embedded semi‐thin sections or electron microscopy, even though being the gold standard for assessing remyelination, is toxic, extremely time‐consuming and expensive. Methods: We screened available myelin dyes for a staining candidate which offers a faster and easier alternative to visualize remyelination in cryo‐sections. Results: We identified sudan black as a candidate with excellent myelin resolution and we show that our adapted sudan black staining can demonstrate myelin repair in rodent spinal cord cryosections as reliable as in semithin sections, but much faster, easier, less toxic and less expensive. Besides that, it can resolve the small myelinated axons in the corpus callosum. The staining can yet readily be combined with immunostainings which can be challenging in semithin sections. We validated the method in human spinal cord tissue as well as in experimental demyelination of the rat spinal cord by a lysolecithin time course experiment. As proof‐of‐principle, we demonstrate that sudan black is able to reliably detect the remyelination enhancing properties of benztropine. Conclusion: Our adapted sudan black staining can be used to rapidly and non‐toxically screen for remyelinating therapies in demyelinating diseases. Abstract : Therapeutic intervention to promote remyelination is a priority target in multiple sclerosis (MS) necessitating high throughput screening of candidate drugs. This study identifies Sudan black staining of cryosections as a suitable non‐toxic, rapid and economical screening method capable of detecting myelin repair in human spinal cord and a rat model.